Análisis de la relación entre la migración y la pobreza dentro del contexto de América Latina, durante el periodo 1999-2019 - Trujillo Torres, María José (2023)
Migration has been a major problem worldwide, since, by 2020, Latin America registered 2.3% of migratory flows, which was alarming for the region. In this way, the impact of migration as the main consequence of poverty is evaluated, through an econometric analysis of panel data, in order to recommend policies that contribute to reducing migration in Latin American countries. To this end, statistical information was used from databases of the World Bank (2020) and the Economic Commission for Latin America and the Caribbean [ECLAC] (2020). Likewise, to meet the specific objectives, three econometric techniques were applied: Westerlund's cointegration model (2007), fully modified least squares test (FMOLS) and dimitrescu and Hurlin's causality test (2012). The results indicate that there is a negative effect between poverty and migration, for the group of 17 countries in Latin America. Likewise, after implementing the Westerlund test, the existence of long-term cointegration between migration and poverty was witnessed. Whereas, when using the FMOLS test, a negative relationship between migration and poverty was witnessed. It was also examined that there is a causal relationship between these variables. Finally, regarding the policy implications, it is considered that those responsible for generating policies should focus on promoting the creation of productive enterprises, aimed at the insertion of the young population.